Temperature dependent Raman modes of reduced graphene oxide: Effect of anharmonicity, crystallite size and defects. (30th October 2021) - Sharma, Meenu; Rani, Sonam; Pathak, Devesh K.; Bhatia, Ravi; Kumar, Rajesh; Sameera, I.
Abstract: A consolidated effect of anharmonicity, crystallite size and defects has been studied using temperature dependent Raman spectroscopy of reduced graphene oxide (rGO). The micro-Raman spectra obtained over a wide temperature range of 173–723 K (below and above room temperature) indicate linear shifts in the peak position of G- and D- modes, with negative temperature coefficients of −0.009 and −0.010 cm −1 K −1, respectively. The average crystallite size and defect density were calculated and their correlation with the temperature coefficient of G-peak position and line width were discussed. Further, contributions from true-anharmonic and quasi-harmonic parts in shifting the G- and D- peak positions were estimated using theoretical models, which indicate the dominance of true-anharmonic part. Role of electron-phonon, anharmonicity and defect contributions to the temperature dependent variation of line width of G-peak have been discussed. Graphical abstract: Image 1 Highlights: Temperature dependent shift in peak position and width of Raman modes of rGO has been studied. Crystallite size and defect density were extracted from ID /IG, as a function of temperature. True-anharmonic and quasi-harmonic contributions to the shifts in G- and D- peaks were estimated. Line width variation of G-peak was explained as an effect of defects, e-ph and ph-ph contributions.